Philosophy of Science as A Basis for the Formation of Values and Morals in Physical Education Practices - Muso Untung; Mu’arifin Mu’arifin (Journal of Physical Education and Health Science, 2025)
This study aims to examine the role of philosophy of science as a basis for the formation of values ​​and morals in physical education practices. The research background is based on the increasingly visible moral crisis phenomenon in educational environments, including in physical education learning, which tends to be solely oriented towards physical aspects. This study uses a qualitative approach with the Systematic Literature Review (SLR) method for seven national and international journal articles published between 2021 and 2025 and obtained through Google Scholar. The review process was carried out systematically, referring to the PRISMA stages.The results of the study indicate that the philosophy of science through its ontological, epistemological, and axiological dimensions provides a conceptual foundation that confirms that physical education not only functions to develop physical abilities, but also plays an important role in the formation of students' values ​​and morals, such as discipline, sportsmanship, honesty, responsibility, and cooperation. The findings also indicate that the weak application of philosophical foundations in physical education learning contributes to the decline in the internalization of students' moral values. This study concludes that the integration of the philosophy of science in physical education practices is an essential need to strengthen the formation of values ​​and morals and support the achievement of educational goals holistically.